Novel one-dimensional Cu@C nanofibers: direct solid-state synthesis and applications in electrocatalytic water splitting. Issue 6 (23rd December 2020) - Zhang, Tianyu; Cheng, Ruohui; Li, Bingbing; Wang, Cuilian; Guo, Ying; Liu, Junfeng; Wang, Lianying
Abstract : Novel 1D Cu@C nanofibers with carbon encapsulated Cu nanoparticles dispersed on carbon nanofibers were synthesized by in situ pyrolysis of organic-layered copper hydroxides for overall water splitting with superior activity and excellent durability. Abstract : Encapsulating metal nanoparticles with a graphitic carbon shell to remit the loss of active sites has drawn attention in catalysis. Herein, we report the development of a facile strategy to prepare graphitic carbon encapsulated Cu nanoparticle (Cu@C) nanofibers by in situ pyrolysis of organic-layered copper hydroxides, which exhibited superior activity and durability for water splitting.